2001
DOI: 10.21273/jashs.126.3.358
|View full text |Cite
|
Sign up to set email alerts
|

Plant Oil Emulsions Prevent Senescent Scald and Core Breakdown and Reduce Fungal Decay in `Bartlett' Pears

Abstract: Preclimacteric `Bartlett' pears (Pyrus communis L.) were dipped for 3 min in either corn (Zea mays L.) or soybean [(Glycine max (L.) Merrill] oil emulsion immediately after harvest and stored at 0 °C. Untreated control fruit developed higher percentages of senescent scald, core breakdown, and decay after 15 weeks storage. Both treatments inhibited senescent scald, core breakdown, and decay in a similar and concentration de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The detection limits of the headspace SPME technique have been claimed to be at the subpicogram level (Zhang and Pawliszyn 1995). In the last decade this method has been applied in fruit aroma studies including pear (Yang and Peppard 1994;Ibanez et al 1998;Chervin et al 2000;Ju and Curry 2000;Ju et al 2001). Suwanagul and Richardson (1998a) have discussed advantages and disadvantages ofthis technique while isolating headspace volatiles of ripening pears.…”
Section: B Isolation and Concentration Of Pear Volatilesmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection limits of the headspace SPME technique have been claimed to be at the subpicogram level (Zhang and Pawliszyn 1995). In the last decade this method has been applied in fruit aroma studies including pear (Yang and Peppard 1994;Ibanez et al 1998;Chervin et al 2000;Ju and Curry 2000;Ju et al 2001). Suwanagul and Richardson (1998a) have discussed advantages and disadvantages ofthis technique while isolating headspace volatiles of ripening pears.…”
Section: B Isolation and Concentration Of Pear Volatilesmentioning
confidence: 99%
“…Quantification of the identified pear volatiles has been mainly performed by calculating the peak area in the chromatogram obtained with a flame ionization detector (FID) (Romani and Ku 1966;Phan-Chon-Ton 1968;Giannone and Baldrati 1967;Jennings and Tressl1974;Russell et al 1981;Romani et al 1983;Shiota 1990;Horvat et al 1992;Avelar et al 1994;Imayoshi et al 1995;Beuerle and Schwab 1997a;Kjaersgaard et al 1997;Lange 1997;Suwanagul and Richardson 1998b;Chervin et al 2000;Ju and Curry 2000;Ju et al 2001). In most cases, the quantification was approximate because no FID response was determined, and only in recent years more accurate measurements have been performed.…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed that the inoculation led to the continuous decrease in fruit firmness, total soluble solids (TSS) content, titratable acidity (TA) content and ascorbic acid (Vc) content as well as the continuous increase in weight loss (Table ) and malondialdehyde (MDA) content (Table ) during the 4 day period of observation. Moreover, fruit senescence conversely contributes to pathogen infection and decay (Ju and Curry ). We also found that the rotten area in the control group increased rapidly and some fruits even rotted away 4 days after inoculation.…”
Section: Resultsmentioning
confidence: 99%
“…The range of firmness values recommended as indicators of harvest maturity is 85 to 98 N for 'Bartlett' pears (Sugar and Powers, 1994). The optimum temperature stated for 'Bartlett' pears in the "Recommendations for Maintaining Postharvest Quality" from University of California is from -1 to 0°C (Mitchan et al, 2013), but the storage of these fruit is typically limited to 60-90 days in air, even under ideal storage conditions at −1 °C (Ju et al, 2001). In most cases, the end of storage life is due to the onset of physiological disorders, particularly superficial scald and internal browning.…”
Section: Introductionmentioning
confidence: 99%